Analysis and stabilizing design of self-excited oscillation in a loading cam using a wedge effect - Katsuhiko SANDO; Takeshi YAMAMOTO; Kenji SAWADA; Tomoyuki TANIGUCHI; Nobuyuki SOWA; Hiroki MORI; Takahiro KONDO (Mechanical Engineering Journal, 2021)
This paper describes a design method of a friction reducer device using a loading cam to suppress unstable vibration. Nonlinear simulation and energy analysis of numerical solutions demonstrates that destabilization is caused by the large phase difference between the slipping velocity in the translation direction and that in the rotation direction. It was found that similarly unstable vibration occurs in various structures using wedge rollers with translational and rotational motion. The analytical equation could be simplified by focusing on the motion factor that affects the slip velocity of the power transmission surface, which is the factor of vibration. Consequently, the design method for suppressing vibration could be expressed by a mathematical formula. This equation is validated by using the results of experiments conducted in the previous work of the current authors. Furthermore, from this equation, we proposed that vibration could be suppressed by the parameter balance of the power transmission device without using damping. The power transmission surface slips when a quick torque is input and damping is used. The proposed design can handle a quick torque response and reduce the weight of the reducer. Specifically, the shape of the wedge roller is made lighter, so that the moment of inertia of the roller is not lowered, or the wedge roller is set as a small roller.